2020
DOI: 10.1182/blood.2019000621
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell–derived NK cells with high-affinity noncleavable CD16a mediate improved antitumor activity

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) is a key effector mechanism of natural killer (NK) cells that is mediated by therapeutic monoclonal antibodies (mAbs). This process is facilitated by the Fc receptor CD16a on human NK cells. CD16a appears to be the only activating receptor on NK cells that is cleaved by the metalloprotease a disintegrin and metalloproteinase-17 upon stimulation. We previously demonstrated that a point mutation of CD16a prevents this activation-induced surface cleavage. This noncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
192
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(195 citation statements)
references
References 58 publications
3
192
0
Order By: Relevance
“…Other variants include a CAR designed by Zhu et al [75] with a mutant variant of CD16 that is not cleaved by the disintegrin and metalloproteinase-17. These CAR-NK cells, combined with rituximab, demonstrated superior anti-tumor activity in in vivo models of B-acute lymphoblastic leukemia (B-ALL).…”
Section: Chimeric Antigen Receptor (Car)-modified Nk Cellsmentioning
confidence: 99%
“…Other variants include a CAR designed by Zhu et al [75] with a mutant variant of CD16 that is not cleaved by the disintegrin and metalloproteinase-17. These CAR-NK cells, combined with rituximab, demonstrated superior anti-tumor activity in in vivo models of B-acute lymphoblastic leukemia (B-ALL).…”
Section: Chimeric Antigen Receptor (Car)-modified Nk Cellsmentioning
confidence: 99%
“…Though the CD16 downmodulation may not be seen in every tumor setting, our ascites data indicates that in settings with low CD16 expression the TriKEs can still mediate tumor killing, albeit in a reduced fashion. However, combination with ADAM17 inhibitors, which have been clinically tested for years, or cellular products that have uncleavable CD16 receptors, recently described and currently being clinically tested (NCT04023071), should greatly improve the activity of TriKEs in settings where CD16 is down-regulated [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to prevent ADAM-17-mediated shedding of CD16, Jing and colleagues showed that replacing the serine at position 197 of the cleavage site of CD16 with proline completely prevented ADAM-17-mediated cleavage of both CD16a and b, enhancing NK cell function to antibody-opsonized tumor cells (156). More recently, the same group provided evidence that amino acid replacement to generate uncleavable CD16 can be feasibly employed in induced human pluripotent stem cells (hiPSC), as a renewable and gene-editable source of off-the-shelf NK cell products with enhanced functionality (157).…”
Section: Matrix Metalloproteinases (Mmps) and A Disintegrin And Metalmentioning
confidence: 99%